Contribution of BSMU employees to the study of health resources of Bukovyna in 1975-2005 - Herush, Igor; Moysey, Antoniy (Aktualʹnì pitannâ suspìlʹnih nauk ta ìstorìï medicini (Online), 2024)
The article provides an assessment of the state and development of scientifi c research by the team of the Chernivtsi State Medical Institute (CHMI) and the Bukovinian State Medical Academy (BSMA) in the fi eld of the use of health resources of the Chernivtsi region in the period 1975-2004. The subject of the research concerned the study of the chemical and medicinal properties of the mineral waters in the Bukovyna, conducting clinical observations and developing recommendations for their therapeutic use. These studies led to the organization of health resorts of the resort type on the basis of mineral water deposits such as Brusnytsia, Klynivka, Shcherbintsi and others, to the widespread use of mineral water in everyday routine by the population of the region. No less important area of scientifi c research is activity of the scientists of ChDMI and BSMA, what was the study of the medical properties of various representatives of the fl ora of the Bukovyna, namely, fl ower pollen (bee’s foot), mountain arnica, foxglove, rhodiola pink, viper- viper, purple echinacea, celandine, yarrow, calendula, chicory, immortelle, hemlock, etc. In experimental and clinical studies, the subjects came to recommendations for therapeutic use. Another direction in the study of health resources of the Chernivtsi region was the study of the karst caves «Bukovynka» and «Popelyushka». Medical and biological studies were conducted, especially in case of «Popelyushka». It has been provided and described its gas warehouse, microclimate, clinical examinations. The scientists were convinced that the sanitary- hygienic characteristics of the cave met the requirements of speleo- therapeutic hospitals and did a lot to ensure that local authorities. These considerations were involved in the development process of this fi eld of public health. Conclusions. Thus, several characteristic features can be noted in the study of health resources of the Chernivtsi region in the period 1975-2004. First, it is a continuation of the research of deposits and sources of mineral water, started in the fi rst 30th anniversary of the existence of ChDMI F. V. Lapshinim, as well as the study of their healing capacity by therapists under the leadership of O. I. Samson. Secondly, the connection to this topic of phytotherapy, as a signifi cant addition to health resources. In the third, BDMA scientists thoroughly investigated the healing potential of two karst caves of our region – «Bukovynka» and «Popelyushka», – at the same time not forgetting their importance for the training of athletes and even cosmonauts. We also wanted to note the rise of scientists and the management of the institution to the level of social signifi cance of the use of natural resources of the region in the improvement of the population, which corresponded to the best global models of the approach to the health problems of the human body.